(untitled) (Acta Entomologica Serbica, 2020)
The present study is based on gasteruptiid samples collected in various parts of Turkey since the 1990s. Together with literature sources, a total of 36 species of the genus Gasteruption Latreille, 1797 are compiled for the country. In addition, the European species Gasteruption boreale (Thomson, 1883) is newly recorded for Turkey and Asia. Moreover, the recently described G. brevibasale van Achterberg & Saure, 2014, G. ischnolaimum van Achterberg, 2014, and G. smitorum van Achterberg, 2014, are recorded for the first time from Erzurum after the original description. Gasteruption henseni van Achterberg, 2014 is, together with the abovementioned four species, confined to eastern Anatolia. Gasteruption hastator (Fabricius, 1804), G. merceti Kieffer, 1904 and G. tournieri Schletterer, 1885, are found to be the most widespread and abundant species throughout Turkey. On the contrary, G. aciculatum van Achterberg, 2014, G. boreale and G. nigritarse (Thomson, 1883) are so far rarely collected in Turkey, recorded from one province each. The first was described after a single female from Van and apart from the holotype no other specimens are known. The eastern part of Turkey proved to be an important center of diversity for Gasteruption species. Distribution maps are presented for the indigenous, rarely, sparsely, widely and frequently recorded species.